STRENGTHENING STUDENTSâ LITERACY THROUGH REFLECTIVE ESSAY WRITING: AN IMPLEMENTATION OF WRITING TO READ PROGRAM IN HIGHER EDUCATION - Shofiya, Arina (Jurnal Bahasa Lingua Scientia, 2017)
Literacy is a condition where a person has capability to read for knowledge, write to share knowledge, and think critically. Studentsâ literacy is a never-end issue in the field of English Language Teaching. Studies have been carried out to investigate literacy practices in various level of education including higher education. Among the problems of studentsâ literacy in higher education are the amount of their reading and writing practices and their motivation to read and write. The current paper is intended to share an experience in strengthening studentsâ literacy at the English Department of State Islamic Institute (Institut Agama Islam Negeri/IAIN) Tulungagung, East Java. The preliminary investigation of the present study revealed that many students have low motivation to read. In addition, their comprehension was relatively low as represented in their paper works. Under a Classroom Action Research Design, the present study was conducted to propose writing to read program to strengthen the studentsâ literacy. In such program, the students were required to write a reflective essay based on the selected topics that they had to read prior to classes. The findings showed that writing reflective essay helped students strengthen their literacy as well as improve their motivation to read and to write because the reading and writing activities were done in a more relax and supportive environment that was at home.